1986
DOI: 10.1016/0304-3959(86)90095-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the use of visual analogue scale in chinese patients

Abstract: The linear analogue score can be used in Chinese patients with relative accuracy provided it has been well explained. The error from employing a vertical presentation is significantly less than that from a horizontal one. The choice of upward or downward orientation is a matter of convenience. Younger patients and those with higher intelligence are quicker to understand the concept and can make better judgement in placing a mark where they wish it to be. A linear analogue scale seems to be a suitable method to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 3 publications
3
83
0
Order By: Relevance
“…One study found that Chinese patients assessed pain more accurately with a vertical version of VAS than with the more commonly used horizontal version (Aun et al, 1986). The following two studies provide evidence that cultural background influences the construct validity of the FPS.…”
Section: Cultural Backgroundmentioning
confidence: 81%
See 2 more Smart Citations
“…One study found that Chinese patients assessed pain more accurately with a vertical version of VAS than with the more commonly used horizontal version (Aun et al, 1986). The following two studies provide evidence that cultural background influences the construct validity of the FPS.…”
Section: Cultural Backgroundmentioning
confidence: 81%
“…Therefore, cultural background can influence the construct validity of the FPS. Moreover, in China, one study found that Chinese patients assessed pain more accurately with a vertical version of the VAS than with the more commonly used horizontal version (Aun, Lam, & Collett, 1986).…”
Section: Background and Significance Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…VAS has also been used in many studies assessing pain, and compared with various symptom scoring systems [13]. VAS has even been evaluated in a Chinese population to determine whether the horizontal line affects the results in patients who are used to reading vertically [14]. The disadvantage of the VAS, and indeed of other methods, is that the investigator does not know when the estimates were made, if they really were done in accord with the instructions.…”
Section: Discussionmentioning
confidence: 99%
“…16 In some cases, it may be necessary to make changes according to pain assessment scales. 17,18 Patients may be reluctant to take medication and analgesics for a number of reasons. Lack of knowledge and skill in pain assessment and treatment, unavailability of morphine, and fear of opioid addiction are some of the complex barriers in emerging countries.…”
mentioning
confidence: 99%